Liberalizing Trade in Legal Services under Asia-Pacific FTAs: The ASEAN Case - HSIEH, Pasha L. (Institutional Knowledge at Singapore Management University, 2015)
The article examines the liberalization of trade in legal services in the Association of the Southeast Asian Nations (ASEAN) and its reform prospects to meet the challenges of multi-jurisdictional practice. It argues that while the ten-country bloc pledges to progressively liberalize the legal sector, ASEAN commitments under free trade agreements (FTAs) constitute merely ‘paper commitments’. To achieve the goal of the ASEAN Economic Community to form a single market and production base, a feasible, incremental roadmap is imperative to integrate the legal services market. The article first analyzes the economic impact of foreign law firms on ASEAN’s legal capacity building and the evolution of emerging ASEAN law. By assessing legal services negotiations under the World Trade Organization, the European Union, and Asia-Pacific FTAs, the article identifies issues of complexity in international arenas. The Singapore experiment further explores the effectiveness of FTAs with Australia and the USA and self-initiated FTA-plus measures such as Joint Law Ventures and Qualifying Foreign Law Practices. These case studies, along with law firms’ operations vis-à-vis regulatory changes, demonstrate the best practices. Finally, the article provides reform proposals that will accelerate the integration of ASEAN’s legal services market and enhance its competitiveness under the multilateral trading system.